Peranan Kecerdasan Intelektual, Emosional Dalam Meningkatkan Kinerja Pegawai Dinas Perhubungan - Sopia Betaubun (Musamus Journal of Business & Management, 2019)
The purpose of this study was to determine the Role of Intellectual, Emotional Intelligence in Improving the Performance of Employees of the Merauke Regency Transportation Office. Methods This study uses a simple linear regression analysis method, a sample population of 65 civil servant employees. The results were obtained from the results of tests with regression tests, the variables of intellectual intelligence and emotional intelligence together with significant intelligence on employee performance. Attention to the Merauke Regency Office There was a significant influence between the intellectual intelligence variables on the Merauke Regency Transportation Department employees. There is no significant effect of the variable emotional intelligence on the performance of the Merauke Regency Transportation Office. Key words: Intellectual Intelligence, Emotional Intelligence, and Performance